DETERMINAN MARGIN KEUNTUNGAN PRODUK PEMBIAYAAN MURABAHAH - Rabbani, Fachri Maulida; Nawirah, Nawirah Nawirah (Faculty of Economics Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2018)
Murabahah financing product at PT. Pegadaian Syariah branch Landungsari Malang, Murabahah Logam Mulia untuk Investasi Abadi (MULIA) is defined as a gold trade financing in a cash or credit in accordance with Sharia laws. This research aims at exploring the determination process of profit margin and the implementation of Standard Operating Procedure in the practice of murabahah financing at PT. Pegadaian SyariahÂ branch of Landungsari Malang. This study uses qualitative method with two approaches. First, the researcher conducted an observation and in-depth interview to Strategi Bisnis Unit (SBU) assistant manager. The result of this study confirms that researcher get total of profit margin Rp. 85.414 in which there is administration cost Rp. 50.000, sales margin 2,5% Rp. 15.725, and installment margin 3,94% namely Rp. 24.783. Researcher get discount margin Rp. 5.094 thatâ€™s means net installment margin is Rp. 19.689. The determination of profit margin for murabahah financing has considered the terms of sharia laws by using consensus principle which is mentioned in Quran surah An Nisa verse 29. This verse explains that any transaction should not bother customers. With this basis, therefore, the practice of murabahah financing has been compatible with the regulations written on Standard Operating Procedure of the firm.